The Influence of Communication and Informatics Communication Strategies through Instagram, Platform X and TikTok on Countering the Spread of Online Hate Speech - Marethy, Fantry; Suhendra, Suhendra (Eduvest - Journal of Universal Studies, 2025)
Hate speech has a negative effect on everyone. Social media such as Instagram, X, and TikTok play a role in opening up space in expressing opinions in the digital world. Technological developments certainly make the role of the Ministry of Communication and Information of the Republic of Indonesia (Kominfo) even more persistent to prevent and overcome the spread of online hate speech that can damage the order of people's lives. The research method carried out is Exploratory Data Analysis (EDA) and literature review, namely identifying, evaluating and interpreting to see effective communication strategies for Kominfo to increase public literacy that can suppress widespread hate speech. The comparative data used is data on hate speech reports in 2023 and 2024.